Analysis of the coastal vulnerability index to erosion and flooding in the Porto Seguro (BA) region and surrounding areas - Leal, Gabriela Nunes Rebouças; Marcolin, Catarina da Rocha; Dadalto, Tatiana Pinheiro (Revista Brasileira de Geomorfologia, 2025)
The coastal zone is a dynamic and complex environment with a diversity of ecosystems of significant economic importance. These factors increase real estate speculation in such areas, requiring efficiency in the management of natural and socioeconomic resources. The objective of this study was to estimate and analyze the Coastal Vulnerability Index (CVI) along a 25 km stretch of coastline between the municipalities of Porto Seguro and Santa Cruz Cabrália (Bahia, Brazil), taking into account physical, environmental, and socioeconomic factors. A total of 11 indicators were assessed, and the CVI was calculated for both moderate (MS) and pessimistic (PS) scenarios, considering constant and rising sea levels (CSL and RSL), using the AHP weighting technique. Our results indicated that under the moderate scenario with constant sea level (CSL-MS), 12.90% of the coast had low vulnerability, 59.77% moderate vulnerability, and 27.33% high vulnerability. In contrast, under the pessimistic scenario (CSL-PS), 80.95% of the coast showed high vulnerability. When considering the scenario of eustatic sea level rise (RSL-MS), 35.78% of the coast was classified as highly vulnerable, whereas in the pessimistic scenario (RSL-PS), this estimate rose to 98.48%. The Ponta Grande and Orla Norte beaches showed high vulnerability because of the presence of river mouths, and should be prioritized for conservation and adaptation efforts. The information provided here is essential for coastal planning and management in the region.